Balancing majority and minority rights: lessons from Malaysia - Azeem Fazwan Ahmad Farouk,; Azrina Husin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This article seeks to unravel the complex, and often opaque state of ethnic relations in Peninsular Malaysia, a plural society, by focusing on the promotion and protection of minority rights. This country, as few others, is characterized by a very marked ethnic, religious, and cultural diversity, which even a casual observer cannot fail to notice. Ever since independence, the co-existence of these different communities turned out to be very complex and riddled with strong tensions. However, incidents of interethnic violence as well as deadly ethnic riots, were very rare across the national territory. The exception to this claim is the May 13th, 1969 ethnic riots that in turn have become the nation’s negative myth - a disruptive conflict that must never occur again. By using a case study approach of historical events, the findings of this article suggest that in order to avoid inter-ethnic violence, a politics of power sharing and affirmative action characterized by permanent negotiations and compromises are the order of the day. Co-existence, however, is still grounded in the social logic of unity in separation. This article seeks to illustrate the workings of the above-mentioned political setting where ethno-cultural and religious diversity are managed so as to ensure minority rights are secured and protected.